2015
DOI: 10.1177/0891242415620484
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Owner Race and Geographic Context on Access to Small-Business Financing

Abstract: Multiple studies document both the scarcity of small-business financing in inner-city minority communities and the higher loan application rejection rates among minority business enterprises (MBEs), compared with equally creditworthy Whiteowned firms. When MBEs do receive bank financing, they get smaller loans than Whites. Two aspects of these findings are troublesome. First, urban MBEs are heavily concentrated geographically in minority communities, raising the issue of whether difficulties accessing financin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
39
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(43 citation statements)
references
References 26 publications
4
39
0
Order By: Relevance
“…These studies support the findings of Blanchard et al (2008), which show opportunity sets also limited by discrimination that Latinos are quoted higher interest rates on bank loans, which may discourage LOB from seeking formal funds for the businesses. A finding here that otherwise similar LOB remain less likely to use bank loans than other ethnicities would provide support to the finding that, once controlling for risk factors, owner race/ethnicity is important (Bates & Robb, 2016), which may indicate discrimination based on if ethnicity influences the ability of LOB to get a bank loan and thereby succeed.…”
Section: Opportunity Set Hypothesis 2 (Osh2): Latino Business Owners supporting
confidence: 66%
“…These studies support the findings of Blanchard et al (2008), which show opportunity sets also limited by discrimination that Latinos are quoted higher interest rates on bank loans, which may discourage LOB from seeking formal funds for the businesses. A finding here that otherwise similar LOB remain less likely to use bank loans than other ethnicities would provide support to the finding that, once controlling for risk factors, owner race/ethnicity is important (Bates & Robb, 2016), which may indicate discrimination based on if ethnicity influences the ability of LOB to get a bank loan and thereby succeed.…”
Section: Opportunity Set Hypothesis 2 (Osh2): Latino Business Owners supporting
confidence: 66%
“…For example, Fairlie and Robb (2010) found that lack of personal assets to invest in business accounted for 25% of the difference in how many businesses were started by Mexican Americans compared to non-Hispanic whites. In addition, research has long shown that BIPOC experience pervasive discrimination in credit markets, resulting in a higher loan denial rate relative to non-Hispanic whites even when controlling for factors such as credit scores, personal wealth, and underwriting differences (Bates & Robb, 2016;Cavalluzzo & Wolken, 2005). When approved for credit BIPOC tend to receive smaller loans (Bates & Robb, 2016) and are subjected to higher interest (Cavalluzzo & Wolken, 2005;Fairlie & Robb, 2010).…”
Section: Source and Access To Financial Resourcesmentioning
confidence: 99%
“…In addition, research has long shown that BIPOC experience pervasive discrimination in credit markets, resulting in a higher loan denial rate relative to non-Hispanic whites even when controlling for factors such as credit scores, personal wealth, and underwriting differences (Bates & Robb, 2016;Cavalluzzo & Wolken, 2005). When approved for credit BIPOC tend to receive smaller loans (Bates & Robb, 2016) and are subjected to higher interest (Cavalluzzo & Wolken, 2005;Fairlie & Robb, 2010). Excluded from formal lending this way, most BIPOC entrepreneurs rely on personal savings, supplemented by contributions from relatives and close friends for startup resources which may not be adequate to launch successful enterprises.…”
Section: Source and Access To Financial Resourcesmentioning
confidence: 99%
See 1 more Smart Citation
“…Both academic and private sector research reveals that minority small business owners are denied credit from traditional banking services at higher rates than white small business owners (Bates and Robb, 2015;Asiedu, Freeman, and Nti-Addae, 2012). This denial produces far greater negative results above and beyond the lack of credit availability itself for specific businesses.…”
Section: Small Business Economymentioning
confidence: 99%